(untitled) (Revista científica Olimpia, 2020)
The investigation was carried out given the necessity to integrate to the recreational activities that are developed in the community to the asthmatic children of the Council Popular "Freedom" of the Diluted Municipality of Passengers. This plan was conceived after carrying out a diagnosis to determine the main necessities and these minor potentialities, you could verify with the initial application of the instruments the faulty participation of these children in the recreational activities physique in the community, for its development a study was made to a sample of 68 children of them 27 they are female and 41 males, in one period understood from November of 2013 until August of 2014. Their general objective is the implementation of an intervention plan sustained in the application of games to achieve a bigger incorporation of asthmatic children to the activities recreativas.Se they used methods of theoretical, empiric and mathematical level - statistical that when analyzing and to process the obtained results, it allowed to confirm the effectiveness of the intervention plan, when being increased the number of asthmatic children to the recreational activities physique and the active participation in the same ones, the parents refer to feel satisfied with the activities and it has diminished the frequency and severity of the crises.